2020
DOI: 10.1016/j.mex.2020.101116
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic in marine environment: reworking and optimisation of two analytical protocols for the extraction of microplastics from sediments and oysters

Abstract: Marine sediments and sessile biota (i.e. oysters) are nowadays recognised to be affected by microplastic (MP) pollution. NOAA proposes two distinct MP extraction protocols for sandy and bed sediments, which, however, were already demonstrated to suffer from many limitations. Conversely, to what concern oysters, works already published are usually time consuming, requiring a KOH 24–48 h oxidation step. The aim of this study is to show how iterative adaptation of the NOAA protocol allows to extract MPs, included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The presence of these congeners could be explained taking into account feeding habits, since it was recently demonstrated that herbivorous copepods could be deceived in their feeding by microplastics and nanoplastics, upon which algae and phytoplankton grow [53]. Such micropolymers have been shown to adsorb organic and inorganic pollutants (such as PAHs and PCBs) [54], thus suggesting that they could be an additional source of PAH congeners once ingested by organisms [55].…”
Section: Copepodsmentioning
confidence: 99%
“…The presence of these congeners could be explained taking into account feeding habits, since it was recently demonstrated that herbivorous copepods could be deceived in their feeding by microplastics and nanoplastics, upon which algae and phytoplankton grow [53]. Such micropolymers have been shown to adsorb organic and inorganic pollutants (such as PAHs and PCBs) [54], thus suggesting that they could be an additional source of PAH congeners once ingested by organisms [55].…”
Section: Copepodsmentioning
confidence: 99%
“…Previous investigations conducted on coastal sediments have revealed that some polymers such as PE and PA were extracted more efficiently than PET (Rivoira et al, 2020) whereas other studies reported a similar extraction efficiency among different Extraction efficiency of microplastics (20-1000 µm) from deep-sea sediments based on two different approaches applied to bulk (BS) and partitioned (PS) sediments.…”
Section: Resultsmentioning
confidence: 94%
“…sample mass, polymers of interest, chemical and equipment availability). Overflow separation methods are effective at isolating microplastics from sediment samples [17] , [18] , [19] , [20] , [21] , [22] , yet detailed procedures are limited and rarely validated with a range of high-density polymers. In addition, overflow separation methods seldom use solutions prepared at high densities that provide a greater recovery of microplastics [2] .…”
Section: Methods Detailsmentioning
confidence: 99%